Approach to adult patients with primary hypothyroidism in some special situations: a position statement from the Thyroid Department of the Brazilian Society of Endocrinology and Metabolism (SBEM) - da Silva Mazeto, Gláucia Maria Ferreira [UNESP]; Sgarbi, José Augusto; Ramos, Helton Estrela; Neto, Danilo Glauco Pereira Villagelin; Nogueira, Célia Regina [UNESP]; Vaisman, Mario; Graf, Hans; de Carvalho, Gisah Amaral (Archives of Endocrinology and Metabolism, 2022)
Primary hypothyroidism is a common disorder in clinical practice. The management of most cases of hypothyroidism is usually straightforward, but the best approach in some special situations may raise questions among physicians. This position statement was prepared by experts from the Brazilian Society of Endocrinology and Metabolism to guide the management of three special situations, namely, hypothyroidism in the elderly, subclinical hypothyroidism in patients with heart disease, and difficult-to-control hypothyroidism. The authors prepared the present statement after conducting a search on the databases MEDLINE/PubMed, LILACS, and SciELO and selecting articles with the best evidence quality addressing the selected situations. The statement presents information about the current approach to patients in these special situations.
Keywords: Diagnosis; hypothyroidism; treatment